Strengthening Climate Change Resilience and Adaptive Livelihood for Women’s and Youth in Poso, Central Sulawesi - Sayaza, Mas Davino; Hartono, Tjahjo Tri; Ningrum, Almyanti; Saripudin, Usep; Alba, Tarmizi (Yayasan Ilomata, 2024)
This study investigates the challenges of climate change and its disproportionate impacts on marginalized communities in Poso, Central Sulawesi, focusing on sustainable livelihood development. Through the Sustainable Livelihood Framework, Satelite Image Analysis and Theory of Change, the research explores livelihood assets and vulnerability contexts, employing a case study approach in Masani and Lape Villages. Primary data was collected through interviews and focus group discussions, while secondary data was gathered from literature study. Results reveal the challenges regarding livelihood assets which are agricultural productivity problems, limited access to healthcare, and underutilization of natural resources. Proposed strategies to address the challenges include capacity building, post-harvest technology enhancement, home gardening promotion, and agrotourism development. Furthermore, stakeholder collaboration and policy enhancement are vital for effective implementation. Ultimately, the study advocates for better improvement and utilization of livelihood assets through inclusive and adaptive approaches to enhance community resilience and sustainability, empowering marginalized groups for a more prosperous future.